Fijian medicinal plants and their role in the prevention of Type 2 diabetes mellitus. Issue 11 (16th November 2022) - Mala, Pritika; Khan, Gausal A.; Gopalan, Romila; Gedefaw, Desta; Soapi, Katy
Abstract: Medicinal plants (MPs) are natural sources of active compounds with potential therapeutic benefits in alleviating various illnesses for decades. Fijian people also are using these MPs for the management/prevention of Type 2 diabetes mellitus (T2DM) and associated complications. However, till date, none of these Fijian MP's antidiabetic potential have been explored or evaluated. Here, we investigated the antidiabetic potential of Fijian MPs scientifically. Phytochemicals such as polyphenols were detected to inhibit the activity of α-amylase and α-glucosidase, the two key carbohydrate enzymes linked to T2DM. Therefore, in the present study, the total phenolic content (TPC), α-amylase and α-glucosidase inhibitory activity of five Fijian MPs: Vobo ( Mussaenda raiateensis, MR), Vula walu ( Blechnum orientale, BO), Gasau ( Miscanthus floridulus, MF), Molikaro ( Citrus limon, CL) and Beki ni sina (Dicranopteris caudate, DC) collected from mainland region of Vitilevu, Fiji Islands, were evaluated in vitro . The hydromethanolic (ME) and dichloromethane (DM) extracts of these selected MPs were investigated. The ME extracts of BO (0.102 ± 0.009 mM CE) and DC (0.098 ± 0.09 mM Catechin Equivalence [CE]) showed a higher TPC compared with the control [vanillic acid (0.052 ± 0.003 mM CE, * P value < 0.05)]. However, the TPC of MF, MR and CL were found in the range of 0.020 ± 0.009 to 0.009 ± 0.01 mM CE. The ME extracts of MF and MR inhibited α-glucosidase significantly in comparison with acarbose as evidenced from the IC50 values (IC50 of MF = 1.58 ± 0.03 ng/µl; IC50 of MR = 1.87 ± 0.43 ng/µl and IC50 of acarbose = 3.34 ± 0.15 ng/µl). Moreover, DM extracts of MR (IC50 = 1.31 ± 0.29 ng/µl) also showed significantly higher α-glucosidase inhibitory activity. In contrary, MR (IC50 = 16.18 ± 0.16 ng/µl) and CL (IC50 = 9.21 ± 0.51 ng/µl) also showed significant α-amylase inhibitory activity in ME and DM extracts, respectively. These, results suggest that Fijian MPs could be a potential source of natural inhibitors of enzymes involved in carbohydrate digestion and thus may possibly be used in managing T2DM.